2021
DOI: 10.3390/ijms221910436
|View full text |Cite
|
Sign up to set email alerts
|

Phage Therapy as a Focused Management Strategy in Aquaculture

Abstract: Therapeutic bacteriophages, commonly called as phages, are a promising potential alternative to antibiotics in the management of bacterial infections of a wide range of organisms including cultured fish. Their natural immunogenicity often induces the modulation of a variated collection of immune responses within several types of immunocytes while promoting specific mechanisms of bacterial clearance. However, to achieve standardized treatments at the practical level and avoid possible side effects in cultivated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 221 publications
0
22
0
Order By: Relevance
“…High-titer phages usually stimulate the immune system of immunocompetent hosts [ 292 ]. However, antibody production depends on the route of phage administration, application timing and dosage, and the phage individual features [ 293 ]. The administration of A. salmonicida phage PAS-1 (MOI of 10000), in rainbow trout, showed significant neutralizing properties of its sera 10 days and 15 days after intramuscular administration which declined after 30 days [ 220 ].…”
Section: Challenges Associated With the Use Of Phages To Control ...mentioning
confidence: 99%
“…High-titer phages usually stimulate the immune system of immunocompetent hosts [ 292 ]. However, antibody production depends on the route of phage administration, application timing and dosage, and the phage individual features [ 293 ]. The administration of A. salmonicida phage PAS-1 (MOI of 10000), in rainbow trout, showed significant neutralizing properties of its sera 10 days and 15 days after intramuscular administration which declined after 30 days [ 220 ].…”
Section: Challenges Associated With the Use Of Phages To Control ...mentioning
confidence: 99%
“…Bacteriophages (phages) are bacterial viruses that can specifically infect host bacterial cells, disrupt bacterial metabolism, and lyse host cells [ 10 ]. Phage therapy, which is based on the use of phages to reduce or eliminate pathogenic bacteria, has been proven to be a promising and flexible approach to combat bacterial infections in aquaculture [ 11 ]. Remarkably, several studies have shown that phage treatment can significantly reduce or even prevent the death of fish infected with A. salmonicides and have generally demonstrated the potential efficacy of phages against A. salmonicida infections [ 3 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since phages were first discovered by Twort (1915), phage treatment has been used successfully in humans, other mammals, food preservation, and aquaculture [ 8 , 9 , 10 ]. A number of controlled experiments have demonstrated the value of using phages in aquaculture [ 11 , 12 , 13 , 14 ]. In this study, a lytic bacteriophage designated as SD04 was isolated from pond water cultured with diseased snakehead.…”
Section: Introductionmentioning
confidence: 99%